Living green, a resident’s perspective on eco-friendly condominium living - Abdul Hadi, Farah Farzana (2024)
In this academic project research, a resident’s perspective on eco-friendly condominium have been investigated. There are two research objectives used in this study which are identify resident perceptions on the benefit of living in green condominiums and analyze what are the most critical issues pertaining to living in green condominiums. In the process of obtaining to this study, the researcher used a questionnaire that was designed based on a literature review through previous research studies where the findings from the study are the components that make up the questionnaire that is coordinated according to the objectives of the study stated in the introductory chapter. By using a non-face-to-face approach, from the 196 residents who lived in Block B of Residensi Novum, Bangsar who were used as a study sample, the researcher has obtained feedback from a total of 79 respondents. The data and feedback were analyzed using descriptive statistics, the researcher presented the results of the study using frequency tables and mean analysis. The results of the study have shown that the benefit of living in green condominiums is to enhanced comfort and the most critical issues pertaining to living in green condominiums is operation and maintenance based on the respondent’s perspective and opinions.